Nanomechanics of Single Crystalline Tungsten Nanowires. (12th February 2008) - Cimalla, Volker; Röhlig, Claus-Christian; Pezoldt, Jörg; Niebelschütz, Merten; Ambacher, Oliver; Brückner, Klemens; Hein, Matthias; Weber, Jochen; Milenkovic, Srdjan; Smith, Andrew Jonathan; Hassel, Achim Walter
Abstract : Single crystalline tungsten nanowires were prepared from directionally solidified NiAl-W alloys by a chemical release from the resulting binary phase material. Electron back scatter diffraction (EBSD) proves that they are single crystals having identical crystallographic orientation. Mechanical investigations such as bending tests, lateral force measurements, and mechanical resonance measurements were performed on 100–300 nm diameter wires. The wires could be either directly employed using micro tweezers, as a singly clamped nanowire or in a doubly clamped nanobridge. The mechanical tests exhibit a surprisingly high flexibility for such a brittle material resulting from the small dimensions. Force displacement measurements on singly clamped W nanowires by an AFM measurement allowed the determination of a Young's modulus of 332 GPa very close to the bulk value of 355 GPa. Doubly clamped W nanowires were employed as resonant oscillating nanowires in a magnetomotively driven resonator running at 117 kHz. The Young's modulus determined from this setup was found to be higher 450 GPa which is likely to be an artefact resulting from the shift of the resonance frequency by an additional mass loading.